2021
DOI: 10.1093/sleep/zsab072.053
|View full text |Cite
|
Sign up to set email alerts
|

054 Characterization of Sleep Phenotypes and Sleep-Dependent Memory Consolidation in a Mouse Model of Fragile X Syndrome

Abstract: Introduction Fragile X syndrome (FXS) is a neurodevelopmental disorder caused by disruption of Fmr1 gene function, leading to intellectual disability. FXS individuals report increased incidence of sleep disruptions such as loss of NREM sleep, irregular sleep/wake cycles, and circadian rhythm disturbances that warrant pharmacological intervention. Since sleep has critical roles in the promotion of memory consolidation, it is unknown whether disrupted cognitive function in FXS is exacerbated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…As little as a few hours of sleep disruption can alter cognitive performance in both human subjects and animal models [11][12][13][14][15] . We and others have recently shown that in mice, short-duration experimental sleep deprivation (SD) in the first few hours following learning experiences can impair both hippocampus-dependent memory processing 1,7,8,[16][17][18][19][20] and neocortex-dependent memory and synaptic plasticity [21][22][23][24][25][26][27] . How does sleep disruption interfere with these processes, and how might sleep promote them?…”
Section: Introductionmentioning
confidence: 99%
“…As little as a few hours of sleep disruption can alter cognitive performance in both human subjects and animal models [11][12][13][14][15] . We and others have recently shown that in mice, short-duration experimental sleep deprivation (SD) in the first few hours following learning experiences can impair both hippocampus-dependent memory processing 1,7,8,[16][17][18][19][20] and neocortex-dependent memory and synaptic plasticity [21][22][23][24][25][26][27] . How does sleep disruption interfere with these processes, and how might sleep promote them?…”
Section: Introductionmentioning
confidence: 99%